Redox Challenge in a Cultured Temperate Marine Species During Low Temperature and Temperature Recovery - Sánchez-Nuño, Sergio; Sanahuja, Ignasi; Fernández-Alacid, Laura; Ordóñez-Grande, Borja; Fontanillas, Ramon; Fernández-Borràs, Jaume; Blasco, Josefina; Carbonell, Teresa; Ibarz, Antoni (Frontiers in Physiology, 2018)
Aquaculture is a growing industry that is increasingly providing a sizable proportion of fishery products for human consumption. Dietary energy and temperature fluctuations affect fish health and may even trigger mortality, causing great losses in fish production during winter. To better understand this unproductive winter period in aquaculture, the redox status in a cultured marine species, the gilthead sea bream, was analyzed for the first time by inducing controlled temperature fluctuations and reducing dietary lipid content. Two groups of fish (by triplicate), differing in their dietary lipid content (18% vs. 14%), were subjected to 30 days at 22°C (Pre-Cold), 50 days at 14°C (Cold) and then 35 days at 22°C (Recovery). Plasma and liver redox metabolites (oxidized lipid, oxidized protein and thiol groups), liver glutathione forms (total, oxidized and reduced) and liver antioxidant enzyme activities were measured. Reducing dietary lipid content did not affect gilthead sea bream growth, glutathione levels or enzyme activities, but did reduce the amount of oxidized lipids. A sustained low temperature of 14°C showed a lack of adaptation of antioxidant enzyme activities, mainly catalase and glutathione reductase, which subsequently affected the glutathione redox cycle and caused an acute reduction in total hepatic glutathione levels, irrespective of diet. Antioxidant enzyme activities were gradually restored to their pre-cold levels, but the glutathione redox cycle was not restored to its pre-cold values during the recovery period used. Moreover, the lower lipid diet was associated with transiently increased liver oxidized protein levels. Thus, we propose that fish should be fed a low lipid diet during pre-cold and cold periods, which would reduce oxidized lipid levels without affecting fish growth, and a higher energy diet during the recovery period. Moreover, diets supplemented with antioxidants should be considered, especially during temperature recovery.